Resolution of Agrarian Conflicts on Plantation Land through Restorative Justice in Indonesia - Artaji, Artaji; Sulistiani, Lies; Rajamanicam, Ramalinggam; Fakhriah, Efa Laela (Lex Scientia Law Review, 2024)
The agrarian reform in Indonesia has not been effectively implemented, leading to significant challenges, particularly regarding the unresolved status of Right to Use Enterprises (HGU) held by plantation entrepreneurs. As a result, many plantation lands remain abandoned, which farming communities—lacking formal land ownership—subsequently cultivate. The government views this activity as unauthorized land occupation, commonly referred to as reclamation. Conflicts over plantation land arise from differing perspectives: while farming communities seek justice, the government perceives plantation land as state property that necessitates state control and management. This issue is further complicated by plantation entrepreneurs who believe they retain valid HGU rights. To address this multifaceted problem, a solution model is needed that engages victims, perpetrators, and community stakeholders to foster a sense of justice. This research employs socio-legal methodologies, utilizing an interdisciplinary approach that incorporates non-legal disciplines to enhance doctrinal analysis and better understand the legal realities faced by all parties involved. The findings indicate that a restorative justice model for resolving conflicts between farming communities and HGU holders is highly appropriate, as it facilitates a sense of fairness for all stakeholders. By bridging the divergent understandings and paradigms of the farming communities and the government, restorative justice mechanisms can effectively restore the rights of those affected and promote peace in the resolution process.